Type specimens and type localities of birds (Aves) collected by Eduard Eversmann and Christian Pander during the Negri Expedition to Bukhara in 18201821 - Mlíkovský, Jiří; Frahnert, Sylke (Zootaxa, 2009)
At least nine bird species were described as new to science on the basis of material collected by Eduard Eversmann and Christian Pander during a Russian embassy headed by Aleksandr Negri to Bukhara in 1820–1821. We identified the type specimens and determined the type localities of these species, which are currently housed in natural history museums of Berlin, Germany, and Moskva, Russia. We suggest that, if only two subspecies of Otus brucei are recognized, the larger northern migratory one should be recognized as O. b. brucei (Hume, 1872), and the smaller southern nonmigratory one as O. b. semenowi (Zarudnyj & Härms, 1902), and we show that the name semenowi has been misapplied to the population from the Tarim Basin. We designate a lectotype for the nominal species Scops obsoleta Cabanis.